Insulation
The heat insulating material with controlled component ratios and distribution in a porous structure addresses the challenge of maintaining insulation at high temperatures by preventing heat transfer path formation, ensuring effective insulation across temperature ranges.
Patent Information
- Application Number
- JP2023530033
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-25
- Filing Date
- 2022-07-29
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2042-07-29
AI Technical Summary
Silica aerogel-based heat insulating materials face challenges in maintaining high heat insulation properties at high temperatures due to the formation of heat transfer paths when infrared shielding particles and inorganic fibers connect, leading to increased conduction and radiation heat transfer.
A heat insulating material comprising a porous structure with hydrophobic sites, infrared shielding particles, and inorganic fibers, with specific mass content ratios and distribution to prevent heat transfer path formation, ensuring high insulation at both room and high temperatures.
The material effectively suppresses heat transfer through radiation and conduction by controlling component interactions, maintaining superior insulation properties even at elevated temperatures.
Smart Images

Figure 0007603158000002 
Figure 0007603158000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a thermal insulation material using a porous structure such as silica aerogel. [Background technology]
[0002] Various insulating materials have been used for the purpose of controlling heat flow in in-vehicle parts, residential building materials, industrial equipment, and the like. Silica aerogel, which has a low thermal conductivity, is known as an insulating material. For example, in a battery pack mounted on a hybrid vehicle or an electric vehicle, an insulating material is disposed between adjacent battery cells. This type of insulating material is required to have high insulating properties, especially at high temperatures, so that it can suppress the transfer of heat and suppress thermal runaway when the battery cell generates abnormal heat.
[0003] For example, Patent Document 1 describes a composite heat insulating material in which a heat insulating layer having silica aerogel, short silica fibers, and an infrared absorbing material is sandwiched between two base fabrics. Paragraph
[0048] of the same document describes that the infrared absorbing material is an effective heat retaining material when a high temperature range of 400 to 900°C is to be maintained. Patent Document 2 describes a heat insulating material having an aerogel fiber body in which silica aerogel is filled into a fiber substrate, and a porous coating layer that covers the aerogel fiber body. Paragraphs
[0052] and
[0056] of the same document describe that when an infrared reflector or an infrared absorbing agent is blended into the aerogel fiber body (heat insulating layer), radiant heat from a heat source can be effectively blocked. Patent Document 3 describes a heat insulating material having silica aerogel, ceramic crystals, inorganic fibers, and an infrared acting material. Paragraph
[0041] of the same document describes that silicon carbide and titanium oxide are effective in reducing radiant heat energy. Patent Document 4 describes a heat insulating material that is a mixture of silica aerogel powder with an average particle size of 0.01 mm to 4.0 mm and silicon carbide powder with an average particle size of 2 μm. Paragraph
[0016] of the same document describes that the thermal conductivity can be reduced by adjusting the mass ratio of silicon carbide powder to silica aerogel powder to be greater than 0 and smaller than 110 per 100 of silica aerogel powder. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2021 / 095279 [Patent Document 2] JP 2009-299893 A [Patent Document 3] International Publication No. 2013 / 141189 [Patent Document 4] JP 2020-16326 A Summary of the Invention [Problem to be solved by the invention]
[0005] Silica aerogel has a skeleton formed by connecting a plurality of silica fine particles, and between the skeletons are pores smaller than the mean free path of air. This fine porous structure mainly suppresses convection among the three forms of heat transfer (conduction, convection, radiation), and exhibits high heat insulation. Here, radiation is a phenomenon in which heat is transferred by electromagnetic waves, and the higher the temperature, the greater the radiant energy released. For this reason, in a high-temperature atmosphere, radiation is the main factor in heat transfer. Therefore, at high temperatures, it is difficult to obtain the desired heat insulation with silica aerogel alone, and it is effective to blend infrared shielding particles as described in the above Patent Documents 1 to 4.
[0006] However, when infrared shielding particles are blended, the infrared shielding particles may be connected to each other, forming a heat transfer path. Furthermore, when other materials such as inorganic fibers are blended, the infrared shielding particles are connected to these materials, making it easier to form a heat transfer path. As a result, the heat transfer by conduction increases, and the heat insulation may decrease. Therefore, simply blending infrared shielding particles cannot fully exert the effect of suppressing heat transfer at high temperatures. In this regard, Patent Document 4 describes the thermal conductivity of a mixture in which silica aerogel powder of a predetermined particle size and silicon carbide powder are mixed in a predetermined ratio. However, in this document, the particle sizes of both powders are limited, and the blending ratio is changed to measure the thermal conductivity, and there is no consideration of the particle filling state and the formation of heat transfer paths, or the case of blending inorganic fibers, etc.
[0007] The present disclosure has been made in consideration of the above-mentioned circumstances, and an object of the present disclosure is to provide a thermal insulation material that uses a porous structure such as silica aerogel and has high thermal insulation properties even at high temperatures. [Means for solving the problem]
[0008] In order to solve the above problems, the heat insulating material of the present disclosure is characterized in that it comprises a porous structure having a skeleton formed by a plurality of particles linked together, pores inside, and hydrophobic sites at least on the surface of the surface and inside, infrared shielding particles, and inorganic fibers, and is provided with a heat insulating layer that satisfies the following conditions (a) to (d): The content of each component in the conditions (a) to (d) is calculated assuming that the total mass of the heat insulating layer is 100 mass%. (a) The content of the inorganic fibers is 5% by mass or more and 25% by mass or less. (b) The content of the infrared shielding particles is 10% by mass or more. (c) The combined content of the porous structure and the infrared shielding particles is 70 mass % or more. (d) The ratio of the content of the porous structure to the content of the infrared shielding particles is 1.2 or more. Effect of the Invention
[0009] According to the insulating material of the present disclosure, by specifying the amounts of porous structure, infrared shielding particles, and inorganic fibers in the insulating layer as (a) to (d), it is possible to achieve both the suppression of heat transfer due to radiation and the suppression of the formation of heat transfer paths, thereby achieving high insulating properties not only at room temperature but also at high temperatures.
[0010] Specifically, by satisfying condition (a), the formation of a heat transfer path is suppressed while the reinforcing effect of the inorganic fibers is exerted. By satisfying condition (b), the transfer of heat by radiation can be effectively suppressed, and the heat insulation at high temperatures is improved. By satisfying condition (c), the content of the porous structure and infrared shielding particles that contribute to improving the heat insulation is increased, and the heat insulation is improved. In addition, the content of components that contribute little to improving the heat insulation is relatively reduced, so that the formation of a heat transfer path by the components is suppressed, and the heat insulation is improved. By satisfying condition (d), the connection between the infrared shielding particles can be inhibited by the porous structure. As a result, the heat transfer path is less likely to be formed, and the heat insulation is improved. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic diagram for explaining a method for measuring the reference number of porous structures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The heat insulating material of the present disclosure will be described in detail below. The heat insulating material of the present disclosure is not limited to the following form, and can be embodied in various forms including modifications and improvements that can be made by a person skilled in the art without departing from the gist of the present disclosure.
[0013] <Thermal insulation layer> The heat insulating material of the present disclosure includes a porous structure, infrared shielding particles, and inorganic fibers, and is provided with a heat insulating layer that satisfies the above-mentioned conditions (a) to (d).
[0014] [Porous structure] The porous structure has a skeleton formed by connecting a plurality of particles and has pores inside. The diameter of the particles (primary particles) forming the skeleton is preferably about 2 to 5 nm, and the size of the pores formed between the skeletons is preferably about 10 to 50 nm. Most of the pores are so-called mesopores of 50 nm or less. Mesopores are smaller than the mean free path of air, so that air convection is restricted and heat transfer is inhibited. The shape of the porous structure is not particularly limited, such as a spherical shape or an irregularly shaped block, but a chamfered shape or a spherical shape is preferable. In this case, the dispersibility in the liquid is improved, so that the composition for manufacturing the heat insulating layer (composition for heat insulating layer) can be easily prepared. In addition, the amount of filling can be increased by reducing the voids between the porous structures, which also suppresses the connection of the infrared shielding particles, thereby improving the heat insulating properties. The porous structure may be used in the manufactured state, or may be further pulverized before use. For the pulverization, a pulverizing device such as a jet mill or a spheroidizing device may be used. The crushing process removes the corners of the particles, giving them a rounded shape, which makes the surface of the insulation layer smooth and less prone to cracks.
[0015] The average particle size of the porous structure is preferably about 1 to 200 μm. The larger the particle size of the porous structure, the smaller the surface area and the larger the pore volume, so the greater the effect of improving the heat insulation. However, since the infrared shielding particles are filled in the gaps between the porous structures, if the particle size of the porous structure is large, there is a risk that the area where the infrared shielding particles are not present will become large. In this case, the frequency with which the infrared rays emitted from the heat source hit the infrared shielding particles will decrease, and the infrared shielding effect may decrease. For example, the average particle size of the porous structure is preferably 10 μm or more, 50 μm or more, and considering the stability of the composition for the heat insulating layer and ease of coating, it is preferably 100 μm or less. The average particle size is determined by the median diameter (D 50 For commercially available products, the catalog value may be used.
[0016] When the particle diameters of the porous structures are different, the small-diameter porous structures enter the gaps between the large-diameter porous structures. This allows the amount of filling to be increased, and the small-diameter porous structures can inhibit the connection of the infrared shielding particles, so that the effect of improving the heat insulation is greater. From this perspective, it is desirable to use porous structures with a wide particle size distribution or to use two or more types of porous structures with different average particle sizes in combination. In addition, the stirring conditions of the material during the manufacturing process of the heat insulating layer may be adjusted so that some of the large-diameter particles are pulverized into small-diameter particles.
[0017] The content of the porous structure may be appropriately determined so as to satisfy the above-mentioned conditions (c) and (d) in consideration of the content of the infrared shielding particles, which also contribute to improving the heat insulation. For example, the content of the porous structure alone is preferably 40% by mass or more, more preferably 50% by mass or more, when the mass of the entire heat insulation layer is 100% by mass. On the other hand, if the content of the porous structure is too high, the porous structure may easily fall off. For this reason, the content of the porous structure alone is preferably 75% by mass or less, more preferably 70% by mass or less, when the mass of the entire heat insulation layer is 100% by mass.
[0018] From the viewpoint of realizing an optimal filling state of the porous structures in the insulating layer, for example, a form in which the reference number of the porous structures calculated by the following steps (i) to (iii) is 10 or more, and even more preferably 15 or more. (i) A cross section of the thermal insulation layer in the thickness direction is photographed at a magnification of 200 times using a scanning electron microscope (SEM), and five parallel straight lines, each 400 μm long, are drawn at 40 μm intervals on the obtained cross-sectional photograph. (ii) For each line drawn, the number of porous structures that intersect with the line is counted, and the total number is calculated. (iii) The calculated total is divided by 5 to obtain the reference number of porous structures.
[0019] FIG. 1 shows a schematic diagram for explaining a method for measuring the reference number of porous structures. FIG. 1 does not limit the heat insulating layer in any way, including the size, shape, and filling state of the porous structures. As shown in FIG. 1, in a cross-sectional photograph 10 obtained by taking a cross section of the heat insulating layer in the thickness direction at a magnification of 200 times by SEM, a porous structure 11, infrared shielding particles 12, and inorganic fibers 13 are observed. The procedure for measuring the reference number of porous structures 11 is as follows. First, five straight lines α, β, γ, δ, and ε are drawn on the cross-sectional photograph 10. The lengths of the five straight lines α, β, γ, δ, and ε are all 400 μm, and the intervals between the lines are 40 μm. Next, the number of porous structures 11 that intersect with each of the five straight lines α, β, γ, δ, and ε is counted, and the sum is calculated. Then, the calculated sum is divided by 5 to obtain the reference number. For example, if the number of porous structures 11 intersecting with the drawn straight lines is v for straight line α, w for straight line β, x for straight line γ, y for straight line δ, and z for straight line ε, the reference number is "(v+w+x+y+z) / 5". The reference number is an index showing the filling state of the porous structures in the heat insulating layer, and if it is 10 or more, it can be determined that the particle diameter of the porous structures is not too large, and a state has been achieved in which small-diameter porous structures and infrared shielding particles, etc. are appropriately filled in the gaps between the large-diameter porous structures.
[0020] The porous structure has a hydrophobic site at least on the surface out of the surface and the inside. When the surface has a hydrophobic site, the penetration of moisture into the pores can be suppressed, so that the porous structure is maintained and the heat insulating property is not easily impaired. For example, by performing a surface treatment with a silane coupling agent or the like, the surface of the porous structure can be given a function such as hydrophobicity. In addition, a hydrophobic treatment such as adding a hydrophobic group may be performed during the manufacturing process of the porous structure.
[0021] The type of the porous structure is not particularly limited. Examples of the primary particles include silica, alumina, zirconia, and titania. Among them, the primary particles are silica, that is, silica aerogel in which a skeleton is formed by linking a plurality of silica fine particles is preferable because of its excellent chemical stability. In addition, an agglomerated structure in which a skeleton is formed by linking a plurality of fumed silica fine particles is also preferable.
[0022] The method for producing silica aerogel is not particularly limited, and the drying process may be performed at normal pressure or at supercritical pressure. For example, if the hydrophobization process is performed before the drying process, it is not necessary to dry at supercritical pressure, that is, it is sufficient to dry at normal pressure, so that it can be produced more easily and at low cost. Depending on the drying method used in producing aerogel, the one dried at normal pressure is sometimes called "xerogel" and the one dried at supercritical pressure is sometimes called "aerogel", but in this specification, both are referred to as "aerogel".
[0023] [Infrared shielding particles] Infrared shielding particles absorb heat from a heat source and re-emit it from the surface on the heat source side, thereby blocking radiant heat from the heat source and contributing to improving heat insulation, especially at high temperatures. From the viewpoint of filling the gaps between the porous structures and suppressing the connection between the infrared shielding particles and other components to make it difficult to form a heat transfer path, it is desirable for the particle diameter of the infrared shielding particles to be relatively small. On the other hand, if the particle diameter is too small, it becomes difficult for infrared rays to hit the particles, and further, the scattering of infrared rays becomes insufficient, so that the radiant heat blocking effect is difficult to be exerted. From this viewpoint, it is preferable that the average particle diameter of the infrared shielding particles is 0.3 μm or more and 22 μm or less. As with the porous structures, the average particle diameter of the infrared shielding particles is also determined by the median diameter (D 50 ) may be adopted, and for commercially available products, catalog values may be adopted.
[0024] Examples of infrared shielding particles include silicon carbide, kaolinite, montmorillonite, silicon nitride, mica, alumina, zirconia, aluminum nitride, titanium oxide, zirconium silicate, zinc oxide, tantalum oxide, tungsten oxide, niobium oxide, indium tin oxide, cerium oxide, boron carbide, manganese oxide, tin oxide, bismuth oxide, iron oxide, magnesium oxide, and barium titanate. In particular, from the viewpoint of enhancing the radiant heat shielding effect, it is desirable that the infrared shielding particles have high emissivity particles having an emissivity of 0.6 or more in the infrared wavelength region. Examples of high emissivity particles include silicon carbide, kaolinite, silicon nitride, mica, alumina, zirconia, aluminum nitride, zirconium silicate, cerium oxide, boron carbide, manganese oxide, tin oxide, and iron oxide. In addition, from the viewpoint of scattering the incident infrared rays to enhance the radiant heat shielding effect, a form having particles with a high refractive index in the infrared wavelength region is also effective. For example, high refractive index particles having a refractive index of 2.0 or more in the visible light wavelength region are suitable. Examples of high refractive index particles include silicon carbide, titanium oxide, zirconia, silicon nitride, aluminum nitride, zinc oxide, tantalum oxide, tungsten oxide, niobium oxide, cerium oxide, manganese oxide, tin oxide, bismuth oxide, iron oxide, and barium titanate.
[0025] For example, silicon carbide, titanium oxide, silicon nitride, mica, alumina, aluminum nitride, boron carbide, iron oxide, magnesium oxide, etc. have a relatively large specific heat, so that their heat capacity is large and the particles themselves do not heat up easily. In this respect, they also contribute to improving the heat insulation of the heat insulating layer. In addition, they also have high heat resistance, so they also contribute to improving the heat resistance of the heat insulating layer. In particular, silicon carbide is suitable because its thermal conductivity does not increase much even in a high-temperature atmosphere of about 800°C.
[0026] The content of the infrared shielding particles is 10% by mass or more when the total mass of the heat insulating layer is 100% by mass (condition (b) above). From the viewpoint of increasing the effect of suppressing heat transfer due to radiation and further improving heat insulating properties at high temperatures, the content of the infrared shielding particles is preferably 15% by mass or more, and further 20% by mass or more. Furthermore, the combined content of the porous structure and the infrared shielding particles is 70% by mass or more when the total mass of the heat insulating layer is 100% by mass (condition (c) above). From the viewpoint of further improving heat insulating properties, the combined content of the porous structure and the infrared shielding particles is preferably 75% by mass or more, and further 80% by mass or more. Furthermore, the ratio of the content of the porous structure to the content of the infrared shielding particles [content of the porous structure (mass%) / content of the infrared shielding particles (mass%)] is 1.2 or more (condition (d) above). By mixing the porous structure with the infrared-shielding particles in a ratio of 1.2 times or more by mass, the porous structure can inhibit the connection between the infrared-shielding particles, thereby suppressing the formation of a heat transfer path. From the viewpoint of increasing the content of the infrared-shielding particles relatively and enhancing the effect of suppressing heat transfer due to radiation, it is preferable that the ratio of the content of the porous structure to the content of the infrared-shielding particles is 8 or less.
[0027] [Inorganic fiber] The inorganic fibers are physically entangled around the porous structure, thereby improving the mechanical strength of the heat insulating layer and suppressing the loss of the porous structure. The type of inorganic fiber is not particularly limited, but ceramic fibers such as glass fiber and alumina fiber are preferable in consideration of heat resistance and mechanical strength. The content of the inorganic fibers is 5% by mass or more and 25% by mass or less when the total mass of the heat insulating layer is 100% by mass (the above-mentioned condition (a)). By setting the content of the inorganic fibers within this range, the reinforcing effect of the inorganic fibers is exhibited while preventing excessive formation of heat transfer paths. The length of the inorganic fibers is desirably 16 mm or less in consideration of both the reinforcing effect and the suppression of the formation of heat transfer paths.
[0028] [Other ingredients] The heat insulating layer may contain other components such as organic additives and reinforcing particles in addition to the porous structure, infrared shielding particles, and inorganic fibers. Incidentally, from the viewpoint of ensuring the self-supporting nature of the heat insulating layer, that is, making the heat insulating layer capable of supporting its own weight by itself and being able to be handled by itself, examples include a form containing a binder that binds components such as the porous structure. However, if a binder is present on the surface or gap of a component such as the porous structure, there is a risk that a heat transfer path will be formed through the binder. Therefore, from the viewpoint of suppressing the formation of a heat transfer path and realizing high heat insulation at high temperatures, it is desirable for the heat insulating layer to have a form that does not have a binder.
[0029] (1) Organic additives Porous structures having hydrophobic sites on the surface or inside are difficult to mix with water. Among them, silica aerogel, hollow silica, fumed silica aggregate structures, etc., have a small specific gravity and therefore tend to float on water. For this reason, it is desirable to add an organic additive from the viewpoint of improving the water suspension of the porous structure to facilitate dispersion of the porous structure when preparing a composition for a heat insulating layer using water as a solvent, and from the viewpoint of adjusting the rheology and water retention of the composition for a heat insulating layer in accordance with the manufacturing method of the heat insulating layer.
[0030] As the organic additive, for example, a surfactant may be used. The type of surfactant is not particularly limited, and may be appropriately selected from ionic surfactants (cationic surfactants, anionic surfactants, amphoteric surfactants) and nonionic surfactants. The surfactant may be used alone or in combination of two or more. For example, when an ionic surfactant is used, even a relatively small amount can increase the viscosity of the heat insulating layer composition and stabilize the dispersion of components such as the porous structure in the heat insulating layer composition. Examples of ionic surfactants include sodium carboxymethylcellulose (CMC-Na), polycarboxylate amine salts, polycarboxylate ammonium salts, polycarboxylate sodium salts, and TEMPO oxidized cellulose nanofibers (CNF-Na). When a nonionic surfactant is used, components such as the porous structure are easily incorporated into the solvent when preparing the heat insulating layer composition. In addition, when these components aggregate or separate in the heat insulating layer composition, they are easily redispersed, and the solvent is easily discharged when the heat insulating layer is formed by drying. Examples of nonionic surfactants include polyethylene oxide (PEO) and polyvinyl alcohol (PVA). In addition, the combined use of a nonionic surfactant and an ionic surfactant is preferable because the aforementioned effects of each can be adjusted as desired. For example, the water retention of PEO is not very high. Therefore, when preparing the composition for the heat insulating layer, water is unlikely to enter the gaps between the porous structures, and voids are unlikely to occur when water evaporates during drying. As a result, infrared shielding particles are easily filled into the gaps between the porous structures. In addition, small-diameter porous structures are easily filled into the gaps between large-diameter porous structures.
[0031] When an organic additive is blended, the organic additive may decompose or carbonize when exposed to high temperatures, forming a heat transfer path and reducing the heat insulation. For example, a material with a heating residue of 50% or less by mass at 600°C is suitable because it produces few products that reduce the heat insulation at high temperatures. Specific examples include PEO, CMC-Na, polycarboxylate amine salts, polycarboxylate ammonium salts, polycarboxylate sodium salts, TEMPO-oxidized cellulose nanofibers (CNF-Na), and PVA. The heating residue may be measured by thermogravimetric analysis (TGA). Specifically, about 5 mg of the organic additive is placed in a platinum pan and heated from room temperature to 600°C at a heating rate of 20°C / min in a nitrogen gas atmosphere, and the mass before and after heating is calculated using the following formula (I). Heating residue (%)=W 1 / W 0 ×100 (I) [W 0 : sample mass before heating, W 1 : mass of sample after heating]
[0032] If an organic additive is present on the surface or in gaps of components such as a porous structure, a heat transfer path may be formed through the organic additive. Therefore, from the viewpoint of suppressing the formation of a heat transfer path, it is desirable that the content of the organic additive is 10% by mass or less, and more preferably 7% by mass or less, when the total mass of the heat insulating layer is 100% by mass.
[0033] (2) Reinforcing particles From the viewpoint of improving the mechanical strength of the heat insulating layer, reinforcing particles may be blended in the heat insulating layer. The type of reinforcing particles is not particularly limited, and for example, inorganic particles having a relatively high hardness and specific surface area, such as precipitated silica, gel silica, fused silica, wollastonite, potassium titanate, magnesium silicate, glass flakes, calcium carbonate, barium sulfate, etc., can be used.
[0034] (3) Flame retardants By blending a flame retardant, it is possible to impart flame retardancy to the heat insulating layer. As the flame retardant, a known one such as a halogen-based, phosphorus-based, or metal hydroxide-based one may be used. In consideration of the environmental load, it is preferable to use a phosphorus-based flame retardant. Examples of phosphorus-based flame retardants include ammonium polyphosphate, red phosphorus, and phosphoric ester. Among them, a water-insoluble one is preferable because the flame retardant is unlikely to flow out even if it comes into contact with moisture during use, and for example, ammonium polyphosphate is suitable.
[0035] <Base material> The heat insulating material of the present disclosure is only required to have the heat insulating layer described above, and other configurations are not particularly limited. For example, it can be configured with a base material supporting the heat insulating layer. In this case, the base material may be disposed on only one side in the thickness direction of the heat insulating layer, or may be disposed on both sides so as to sandwich the heat insulating layer. In addition, a single base material may be used as a covering body that wraps the heat insulating layer. An adhesive layer may be interposed between the heat insulating layer and the base material. The adhesive layer may contain a flame retardant in addition to the adhesive component.
[0036] Examples of the material of the substrate include cloth, resin, paper, and steel plate. Examples of the fibers constituting the cloth include glass fiber, rock wool, ceramic fiber, alumina fiber, silica fiber, carbon fiber, metal fiber, polyimide fiber, aramid fiber, and polyphenylene sulfide (PPS) fiber. Examples of ceramic fibers include refractory ceramic fiber (RCF), polycrystalline alumina fiber (Polycrystalline Wool: PCW), and alkaline earth silicate (AES) fiber. Among them, AES fiber is safer because it is biosoluble. Examples of resins include polyethylene terephthalate (PET), polyimide, polyamide, and PPS. Examples of paper include pulp and composite materials of pulp and magnesium silicate. Examples of steel plates include galvalume steel plate (registered trademark), galvanized sheet, stainless steel (SUS) plate, iron plate, and titanium plate. The shape of the substrate is not particularly limited, and examples include woven fabric, nonwoven fabric, film, and sheet. The substrate may be a single layer or a laminate of two or more layers of the same or different materials.
[0037] For example, fabrics (woven fabrics) and nonwoven fabrics made from inorganic fibers such as glass fibers and metal fibers, such as glass cloth, and fire-resistant insulating paper made as a composite of pulp and magnesium silicate have a relatively small thermal conductivity and high shape retention even in a high-temperature atmosphere. In addition, if a substrate with high heat resistance is used, it can be used in applications that require high heat resistance, expanding the applications of the insulating material of the present disclosure. Furthermore, if a substrate with fire resistance is used, safety is further improved. Substrates with high heat resistance may be made from glass fibers, rock wool, ceramic fibers, polyimide, PPS, etc., and specific examples include glass fiber nonwoven fabric, glass cloth, aluminum glass cloth, AES wool paper, and polyimide fiber nonwoven fabric.
[0038] <Insulation material manufacturing method> The heat insulating material of the present disclosure can be produced by pressure molding a material containing a porous structure, infrared shielding particles, inorganic fibers, and the like. Alternatively, the heat insulating material can be produced by applying a liquid (including slurry) composition for a heat insulating layer to a substrate and drying it. For application, a brush coating, a coating machine such as a blade coater, a bar coater, a die coater, a comma coater (registered trademark), or a roll coater, or a spray, may be used. Alternatively, the heat insulating material may be produced by immersing a substrate in the composition for a heat insulating layer, or forming the composition for a heat insulating layer on a substrate by a papermaking method. Drying may be performed at a temperature of 80 to 180°C for several minutes to several tens of minutes.
[0039] The thickness of the heat insulating layer may be appropriately determined depending on the application. For example, from the viewpoint of heat insulation, it is desirable to set it to 0.1 mm or more, 0.5 mm or more, or even 1 mm or more. If the heat insulating layer is too thick, not only will the cost increase, but the strength will decrease and the layer will become brittle. For this reason, for example, it is preferable to set it to 10 mm or less, or 8 mm or less. In particular, from the viewpoint of thinning and increasing flexibility, it is preferable to set it to 5 mm or less, or even 3 mm or less. EXAMPLES
[0040] Next, the present disclosure will be described more specifically with reference to examples.
[0041] (1) Manufacturing of insulation samples A heat insulating material sample having the composition shown in Table 1 below was manufactured. First, silica aerogel, infrared shielding particles, glass fiber, organic additives, and reinforcing particles were put into a kneader (Trimix (registered trademark) manufactured by Inoue Seisakusho Co., Ltd.) and stirred and mixed for 1 minute. While continuing to stir, water was added so that the solid content was 40 to 50%, and colloidal silica (aqueous dispersion of silica particles; LUDOX (registered trademark) LS manufactured by Sigma-Aldrich Co.) was added for samples blended with an inorganic binder (Comparative Examples 4 and 5 in Table 1 below). Then, stirring and mixing were performed for another 15 minutes. Thereafter, stirring was stopped every 2 minutes, and materials attached to the inner wall surface of the container, the blade surface, etc. were scraped off with a spatula while stirring and mixing was performed for an additional 30 minutes to manufacture a clay-like composition for a heat insulating layer.
[0042] Details of the materials used are as follows: Silica aerogel powder: "Aerogel Particles P200" manufactured by Cabot Corporation, particle size 0.1mm~1.2mm. Glass fiber: "Wet Chop" manufactured by Nippon Electric Glass Co., Ltd., length 3 mm, filament diameter 6.5 μm. Silicon carbide (SiC) powder: "Fuji Random GC" manufactured by Fuji Manufacturing Co., Ltd., particle size standard #4000. Titanium dioxide (TiO 2 ) Powder: "High purity titanium oxide HT0110" manufactured by Toho Titanium Co., Ltd. PEO: Polyethylene oxide manufactured by Sigma-Aldrich, viscosity average molecular weight: 1 million. CMC: sodium carboxymethylcellulose, manufactured by Sigma-Aldrich, molecular weight 380,000. Wet silica: "Nipsil (registered trademark) NS-K" manufactured by Tosoh Silica Corporation.
[0043] Next, a base was prepared in which a first spacer plate made of SUS was layered on top of the glass fiber paper. The thickness of the first spacer plate was 4 mm, and a square injection hole of 150 mm square was formed in the center. The produced heat insulating layer composition was filled into the injection hole of the first spacer plate and molded into a plate shape. Thereafter, the first spacer plate was removed, another second spacer plate was placed, and glass fiber paper was layered on top of it to produce a laminate consisting of "glass fiber paper / heat insulating layer composition / second spacer plate / glass fiber paper". The thickness of the second spacer plate was 3 mm, and like the first spacer plate, a square injection hole of 150 mm square was formed in the center. The heat insulating layer composition was placed in the injection hole of the second spacer plate. Separately from this, a first aluminum plate material having a thickness of 5 mm and a square of 320 mm, and a second aluminum plate material having a thickness of 1 mm and a square of 320 mm were prepared. A plurality of grooves were formed on one side of the first plate material. The grooves are each linear with a width of 2.5 mm, a depth of 3 mm, and a length of 200 mm, and are formed in parallel at intervals of 5 mm. The second plate has punched holes with a diameter of 1 mm formed all over it at intervals of 2 mm. The second plate is placed on one side of the first plate, and a laminate is placed on top of it. The second plate is then placed on top of the laminate, and the first plate is further placed so that the side on which the grooves are formed faces the second plate. In this state, pressure drying is performed by hot pressing at a temperature of 165°C and a load of about 98 kN for 30 minutes. After that, it is allowed to cool to room temperature, and the first plate, the second plate, the upper and lower glass fiber papers, and the second spacer plate are removed to obtain a plate-shaped insulation sample with a thickness of 3 mm.
[0044] Of the obtained heat insulating material samples, the reference number of silica aerogels was measured for the samples of Examples 1 and 3 in Table 1 described later. The measurement method is as follows. First, a test piece of a predetermined size was cut out from the heat insulating material sample, and platinum coating was performed as a pretreatment. Then, a cross section was processed by using a "Cross Section Polisher (registered trademark) SM09010" manufactured by JEOL Ltd. at an acceleration voltage of 4 kV and a processing time of 20 hours. Next, the processed cross section was made conductive by osmium coating, and a backscattered electron image was taken with an "SEM S-3400N" manufactured by Hitachi Ltd. at an acceleration voltage of 15 kV and a magnification of 200 times. Five straight lines with a length of 400 μm were drawn in parallel at 40 μm intervals on the obtained cross section photograph, and the number of silica aerogels intersecting with each straight line drawn was counted. Then, the number of silica aerogels was summed up, and the value was divided by 5 to obtain the reference number. As a result, the reference number for the sample of Example 1 was 26.4, and the reference number for the sample of Example 3 was 16.2.
[0045] (2) Measurement of thermal conductivity The thermal conductivity of the manufactured insulation samples was measured using a "Quick Thermal Conductivity Meter QTM-700" and a "High Temperature Probe PD-31N" manufactured by Kyoto Electronics Manufacturing Co., Ltd., as follows. First, two insulation samples were stacked and sandwiched between the upper and lower probes, and a weight of a mass large enough not to crush the insulation samples was placed on top and placed in an electric furnace. Then, the temperature in the electric furnace was raised to 800°C, and after the temperature in the furnace stabilized, the thermal conductivity was measured.
[0046] (3) Evaluation of insulation properties The composition of the insulation samples and the results of the evaluation of their insulation properties based on the thermal conductivity measurements are shown in Table 1. For the insulation property evaluation, samples with a thermal conductivity of less than 0.3 W / m K were deemed to pass (indicated by a circle in the table), and samples with a thermal conductivity of 0.3 W / m K or more were deemed to fail (indicated by an x in the table). [Table 1]
[0047] As shown in Table 1, all of the samples of Examples 1 to 7 that satisfy the above-mentioned conditions (a) to (d) have a thermal conductivity of less than 0.3 W / m·K, and it was confirmed that they have excellent heat insulating properties even at high temperatures. In contrast, the sample of Comparative Example 1 does not contain infrared shielding particles and does not satisfy conditions (b) to (d). The sample of Comparative Example 2 has a ratio of the content of silica aerogel to the content of infrared shielding particles of 0.5 and does not satisfy condition (d). The sample of Comparative Example 3 has a content of infrared shielding particles of 0.5 mass % and does not satisfy condition (b). The sample of Comparative Example 4 does not contain infrared shielding particles and does not satisfy conditions (b) to (d). The sample of Comparative Example 5 has a total content of silica aerogel and infrared shielding particles of 50 mass %, and does not satisfy condition (c). Therefore, all of the samples of Comparative Examples 1 to 5 have a thermal conductivity of 0.3 W / m·K or more, and the desired heat insulating properties at high temperatures could not be obtained. [Industrial Applicability]
[0048] The heat insulating material of the present disclosure is suitable for use as a heat insulating material for vehicles, a heat insulating material for housing, a heat insulating material for electronic devices, a heat insulating material for hot and cold storage containers, etc. In particular, it is suitable for use in battery packs, heat-not-burn cigarettes, fire-resistant heat insulating sheets, etc., which require heat insulating properties in high-temperature environments. [Explanation of symbols]
[0049] 10: Thermal insulation layer (cross-sectional photograph), 11: Porous structure, 12: Infrared shielding particles, 13: Inorganic fibers.
Claims
1. a porous structure in which a plurality of particles are linked to form a skeleton, the porous structure having pores therein, and the porous structure having a hydrophobic site at least on the surface of the surface and the interior thereof; infrared shielding particles, inorganic fibers, and an organic additive; the porous structure having an average particle diameter of 10 μm or more and 100 μm or less, the infrared shielding particles having an average particle diameter of 0.3 μm or more and 22 μm or less, the organic additive being heated in a nitrogen gas atmosphere from room temperature to 600° C. at a heating rate of 20° C. / min, and having a heating residue of 50 mass% or less as calculated from the masses before and after heating according to the following formula (I); and a heat insulating layer which satisfies the following conditions (a) to (d): An insulating material characterized in that a reference number calculated by the following steps (i) to (iii) as an index showing the filling state of the porous structure in the insulating layer is 10 or more. <Formula (I)> Heating residue (%) = W 1 / W 0 ×100 [W 0 : sample mass before heating, W 1 : sample mass after heating] <Conditions> (a) The content of the inorganic fibers is 5% by mass or more and 25% by mass or less. (b) The content of the infrared shielding particles is 10 mass % or more. (c) The combined content of the porous structure and the infrared shielding particles is 70 mass % or more. (d) The ratio of the content of the porous structure to the content of the infrared shielding particles is 1.2 or more. The content of each component under the conditions (a) to (d) is calculated with the total mass of the heat insulating layer being 100 mass %. <Procedure> (i) A cross section of the heat insulating layer in the thickness direction is photographed at a magnification of 200 times using a scanning electron microscope, and five parallel straight lines, each 400 μm long, are drawn at 40 μm intervals on the obtained cross-sectional photograph. (ii) For each of the drawn straight lines, the number of the porous structures that intersect with the straight line is counted, and the total number is calculated. (iii) The calculated total is divided by 5 to obtain the reference number of the porous structures.
2. The heat insulating material according to claim 1 , wherein the infrared shielding particles comprise high emissivity particles having an emissivity of 0.6 or more in the infrared wavelength region.
3. The heat insulating material according to claim 1 , wherein the infrared shielding particles have a high refractive index of 2.0 or more in the visible light wavelength region.
4. The insulation material of claim 1 , wherein the organic additive comprises a surfactant.
5. The insulation material of claim 4 , wherein the surfactant comprises a non-ionic surfactant.
6. 5. The insulation material of claim 4, wherein the surfactant comprises both a non-ionic surfactant and an ionic surfactant.
7. 2. The heat insulating material according to claim 1, wherein the inorganic fibers have a length of 16 mm or less.
8. The heat insulating material according to claim 1 , wherein the porous structure has a silica aerogel in which a plurality of silica fine particles are linked to form a skeleton.
9. The heat insulating material according to claim 1 , wherein the porous structure has a cohesive structure in which a plurality of fumed silica fine particles are linked to form a skeleton.
10. The insulation of claim 1 , wherein the insulating layer is binder-free.
11. The heat insulating material according to claim 1 , further comprising a substrate laminated to the heat insulating layer.
12. The insulation material of claim 1 , wherein the infrared shielding particles comprise silicon carbide particles.
13. The thermal insulation material according to claim 1 , wherein the infrared shielding particles comprise titanium oxide particles.
Citation Information
Patent Citations
Low-cost high-performance nano heat insulation plate and preparation method thereof
CN113666675A
Nanometer vacuum insulation panels
CN206943696U
Combustion plate for infrared ray radiant heater
JP1982187512A
Production of heat insulating material for vacuum furnace
JP1995033551A
Heat insulating material composition
JP1995237957A
